Tolerance Portraits in Kupang City Based on Dimensions of Perception, Attitude, Cooperation, and Government Role - Jefirstson Richset Riwukore; Fellyanus Habaora; Fakhry Zamzam; Tien Yustini (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2021)
Humans were influenced by perceptions, attitudes, cooperation, and the government roles to portray indicators of religious tolerance. Therefore, this study was carried out between January and March 2020 to deeply analyze the dimensions of perception, attitude, cooperation, and the roles of the government, using a case study technique with a descriptive approach. The population of this study were 53 people representing religious figures, community leaders, government, and levels of society. A questionnaire was used containing statements based on Likert scale measurements. Data analysis was carried out in a narrative manner. The results showed that the portrait of the dimensions of perception, attitude, cooperation, and the role of the government supports religious tolerance in the City of Kupang. However, it found that a neutral attitude was shown when it was related to the attendance to the worship of other religions. Based on the dimension of cooperation, there were also people who showed a neutral attitude on the donations or social action for the followers of other religions, and a willingness to maintain a normative business that does not conflict with adherents of other religions. Unsur manusia yang dipengaruhi oleh persepsi, sikap, kerjasama dan peran pemerintah merupakan indikator potret terhadap toleransi umat beragama. Untuk hal tersebut maka telah dilakukan penelitian sejak Januari-Maret 2020 tentang potret dimensi persepsi, sikap, kerjasama, dan peran pemerintah, menggunakan teknik studi kasus dengan pendekatan secara deskriptif. Populasi ataupun sampel dalam penelitian ini sebanyak 53 orang sebagai representatif tokoh-tokoh agama, tokoh-tokoh masyarakat, pemerintahan, dan lapisan masyarakat. Metode survei menggunakan kuesioner yang berisi pernyataan berbasis pengukuran skala Likert. Analisis data dilakukan secara naratif. Hasil penelitian menunjukkan bahwa potret dimensi persepsi, sikap, kerjasama, dan peran pemerintah mendukung toleransi umat beragama di Kota Kupang. Meskipun demikian masih ada sikap umat beragama yang netral jika terkait dengan kesediaan berada di rumah ibadah pemeluk agama lain yang ada di sekitar tempat tinggal. Berdasarkan dimensi kerjasama, juga terdapat umat yang menunjukkan sikap netral terhadap kesediaan memberikan sumbangan atau aksi sosial kepada pemeluk agama lain, dan kesediaan untuk menjaga normatif usaha yang tidak bertentangan dengan pemeluk agama lain.